ULTIMATE TENSILE STRENGTH ANALYSIS OF AN EPOXY COMPOSITE WITH PALM FIBERS AND ARECA CATECHU FIBERS - Lubis, Gita Suryani; Tedi, Tedi; Noah, Muhammad Nouki; Noventa, Vinsen; Sajiwo, Tegar; Kamaludin, Muhammad Doni (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
There are many types of reinforcement that can be used in the making of composites, and one of the more recent and popular ones is fiber-reinforced polymer. There are many types of fibers that can be used for the composite; this experiment will focus on natural fibers, specifically palm branch fiber and Areca catechu trunk fiber (Known locally in Indonesia as Pinang) with epoxy as its matrix. The composite will be constructed with different parameters, such as different NaOH treatment time (1,2, and 3 hours), pinang: palm fiber composition (50:50, 30:70, and 70:30) and fiber orientation (Horizontal, Vertical, and Random). Through the tensile strength, it's been found that the average strength is 3.07 MPa, where the highest value is 4.04 MPa with the NaOH treatment time of 1 hour, pinang: palm fiber composition of 30:70, and fiber oriented vertically.